2013
DOI: 10.5489/cuaj.554
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a virtual reality transrectal ultrasound guided prostatic biopsy simulator

Abstract: Objective: We present the design, reliability, face, content and construct validity testing of a virtual reality simulator for transrectal ultrasound (TRUS), which allows doctors-in-training to perform multiple different biopsy schemes. Methods: This biopsy system design uses a regular "end-firing" TRUS probe. Movements of the probe are tracked with a micromagnetic sensor to dynamically slice through a phantom patient's 3D prostate volume to provide real-time continuous TRUS views. 3D TRUS scans during prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Other studies have also shown that experienced physicians tend to score low during simulation assessment due to a degree of unfamiliarity and lack of realism of the simulation equipment used. 26,27 Setting standards or a credible pass/fail score for performance is an essential asset of a test 12,28,29 and its application is progressively required in competency based learning, especially for procedural assessment. 30,31 Validity evidence for consequences of testing was gathered using the Angoff method to define a passing score.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that experienced physicians tend to score low during simulation assessment due to a degree of unfamiliarity and lack of realism of the simulation equipment used. 26,27 Setting standards or a credible pass/fail score for performance is an essential asset of a test 12,28,29 and its application is progressively required in competency based learning, especially for procedural assessment. 30,31 Validity evidence for consequences of testing was gathered using the Angoff method to define a passing score.…”
Section: Discussionmentioning
confidence: 99%